MEMBANGUN KARAKTER SISWA: PERAN METODE PEMBELAJARAN DISKUSI DALAM PENDIDIKAN - Aqil Ulil Abror; Moh Rosuli; Syaiful Bahri (JURNAL ILMIAH RESEARCH STUDENT, 2025)
National Education aims to develop the potential of students to become human beings who believe in and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. This research method uses a qualitative descriptive critical analysis approach, however there will be challenges that can arise and hinder the formation of student character, the demands of academic achievement that must be achieved by students are more dominant, to the exclusion of the formation of student personality character. The aim of character building is to train a sense of cooperation. With the presence of character, you can train a sense of concern for one another so that students can train cohesiveness in groups. In the process of developing a character, to train self-confidence in students, there are many obstacles that must be faced, therefore it must involve various parties. parents because students spend a lot of time together, parents' involvement in building a confident character in students is very important and crucial.